Comparison of The Relative Brain Sizes and Learning Abilities of Animals of The Rodentia - Suripto, Suripto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Animals from the order rodentia are often used as experimental animals to study the fields of biology, medicine and animal husbandry, but are rarely used as objects of study to determine their position in evolutionary development and their role in the surrounding environment. One aspect of animal evolutionary development is learning behavior. Learning behavior in animals, especially those related to intelligence, is correlated with the relative size of the animal's brain. This research has examined the comparison of intelligence levels and relative brain size between animals, especially four species of animals from the Order Rodentia, namely mice (Mus musculus), mice (Rattus assimilis), hamsters (Mesocricetus auratus) and guinea pigs (Cavia porcellus). The learning ability of test animals was measured using the T-Maze procedure according to a complete group randomized experimental design. Data on the learning ability of the test animals were processed using ANOVA Model I and continued with the Orthogonal Contrast Test. The results of the research show that the average learning ability from highest to lowest is possessed by mice, hamsters, guinea pigs and mice. This learning ability data is in sync with data on relative brain size, namely the relative size of the largest brain in mice and the relative size of the smallest brain in mice. The learning ability of mice and rats, which both come from the same family, namely Disciples, is not significantly different from that of hamsters from another family, namely Cricetidae. Rats, mice and hamsters, which all come from the same suborder, namely Myomorpha, have much higher learning abilities compared to guinea pigs which come from another suborder, namely Hystricomorpha.